Effects of Sub-Cooling on the Performance of R12 Alternatives in a Domestic Refrigeration System - Bolaji, Bukola Olalekan (Science & Technology Asia, 2015)
This paper presents experimental results of investigation of effects of sub-cooling on the performance of four ozone-friendly alternative refrigerants (R32, R152a, R143a, and R134a) in a domestic refrigeration system. The study was performed using a system designed for R12 with the aim of finding a drop-in replacement for the refrigerant. The results obtained showed that the sub-cooler in the refrigeration system positively affected the system performance and all the investigated refrigerants benefited from the performance improvement. An increase in sub-cooling effectiveness reduces the compressors work input and increases the system refrigeration capacity. Also, an increase in the degree of sub-cooling, reduces the pressure ratio, and increases both the refrigerant mass flow rate and coefficient of performance (COP) of the system. The comparison of the performance of R12 and the investigated alternative refrigerants showed that R152a and R134a have the most similar performance characteristics to R12, with R152a having a slightly better performance. These two refrigerants are the best replacements for R12 in a domestic refrigeration system. The performances of R32 and R143a were significantly lower than that of R12.